Symmetric dimethylarginine: a novel renal biomarker - Guess, Sarah Crilly (Kansas State University, 2016)
Chronic kidney disease (CKD) is a potentially life-threatening disease that reportedly affects 10% of dogs and 30% of cats over the age of 15. There is no cure available for CKD, but medical management is available for patients with this disease. Research has focused on earlier detection of CKD with the goal of instituting medical management and monitoring as early in the disease course as possible. Symmetric dimethylarginine (SDMA) has recently emerged as a novel renal excretory biomarker that may aid in early detection of CKD in cats and dogs. SDMA is non-protein bound and is freely filtered by the glomerulus, is not secreted or reabsorbed, and has greater than 90% excretion by the kidneys, making it a potential target for measurement of glomerular filtration rate (GFR). Previous studies have demonstrated a close parallel between SDMA and serum creatinine (sCr), which is the currently favored serum biomarker for assessment of GFR. Research has also demonstrated a correlation between SDMA and GFR. Serum concentrations of SDMA increase above normal when GFR is decreased by 25-40%; much earlier than the 75% decrease in GFR typically required for sCr to increase above its reference interval. The studies reported here demonstrate a potential use for the SDMA:sCr ratio as a predictor of volume responsive azotemia. Furthermore, longitudinal assessment of older dogs and cats for early detection of CKD showed that SDMA was a more sensitive indicator of CKD than sCr. The evaluation of SDMA reported in this thesis presents a novel perspective on SDMA and its use clinically.
Keywords: Symmetric Dimethylarginine; Chronic Kidney Disease; Renal Excretory Biomarker; Veterinary